DETERMINING THE FACTORS INFLUENCING PATIENT SAFETY CULTURE IN HOSPITAL SETTINGS - Khan, Najm Us Saqib; Noor, Qamar Ul Haq; Tasawar, Amna; Hisamuddin, Effat (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the factors potentially influencing patient safety culture in hospital settings an comparison of patient safety factors in public and private hospital. Study Design: Qualitative study. Place and Duration of Study: The study was conducted in two hospitalsin Pakistan; one from public and other from private sector, from Feb 2017 to Jun 2018. Methodology: A multimethod approach was used for data collection including interviews and focused group discussionswith 50 physicians/doctors & staff from different levels of management hierarchy/department and analysis was done by integrating and coding the two sets of data manually. The data was coded and themes were formed. Results: The different themes obtained from the study included: Human factors like leadership, teamwork, communication work-load and professionalism;physical factors like resources, infrastructure and cleanliness; patient factors like severity of illness, availability of attendant and drug allergies; environmental factors like climate, staff and working conditions and safety culture like safe administration of drugs, blood products, sampling, sterilization and prophylactic antibiotics administration. Conclusion: Multiple factors related to human being and environment were identified to influence patient safety in a hospital setting. Participants from the public hospital were more knowledgeable compared to the private hospital.